Pemanfaatan Teh dan Rempah-rempah Khas Indonesia dalam Pemeliharaan Kesehatan Warga di Sumba Timur Menghadapi Pandemi Covid-19: Tea and Indonesian Spices for Improving Health for People in East Sumba for Facing Pandemic COVID-19 - Sulistyowaty, Melanny Ika; Purwanto, Djoko Agus; Agil, Mangestuti; Ekowati, Juni; Isadiartuti, Dewi; Hendradi, Esti; Purwitasari, Neny; Yusniasari, Putri Antika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The coronavirus (SARS-CoV-2) has infected nearly 4 million people worldwide. This virus was first identified in Wuhan, China, in December 2019. Every day positive cases of Covid-19 are increasing in the world. Experts are still trying to find a vaccine to prevent this virus, one of which is by increasing the body's resistance (immunity). The use of family medicinal plants (TOGA) or tea, a drink that we usually drink every day is believed to increase one's body immunity. The content of natural chemicals in tea such as EGCG and curcumin found in the rhizomes have antioxidant activity and is clinically proven to increase a person's immunity.